The degree to which kindergarten curricula in the Kingdom of Saudi Arabia include some concepts of digital citizenship in light of the requirements of the digital age - Ghandurh, Remeen Abbas (Journal of Educational and Psychological Sciences, 2021)
The study aimed to determine the degree to which kindergarten curricula in the Kingdom of Saudi Arabia include some concepts of digital citizenship in light of the digital age requirements. To achieve this goal, the researcher used the descriptive and analytical approach to the study sample represented in 8 books from the kindergarten curricula in Saudi Arabia. A list of digital citizenship concepts, needed in light of the digital age, was built based on a review of educational literature and previous studies related to the topic. The list included a total of 30 indicators categorised into 6 areas: digital behavior, digital communication, digital knowledge, digital health and safety, digital law, and digital security. The researcher analyzed the content based on the list of standards and concluded that the inclusion of digital citizenship concepts was very limited or almost absent in the studied sample. Inclusion was highest for digital knowledge and digital health and safety at 50% for each area, but with only two repetitions. Other areas, however, were not included at all (0%). The most important recommendation of the study is to highlight the need for specialists in kindergarten curricula to familiarize themselves with the current global standards of curricula, and to include the most important and relevant concepts of the digital age, including digital citizenship. It is also necessary to review the weaknesses and the lack of kindergarten books on the self-learning approach in the curriculum developed in Saudi Arabia, as well as to strengthen the available advantages.
Keywords: content analysis; kindergarten curricula; digital citizenship; digital age